Synchronous local recurrence and liver metastasis from extragastrointestinal stromal tumor in the rectovaginal septum: a unique case presentation - Eleni Papamattheou; Ioannis Katsaros; Eirini Chorianopoulou; Kyriaki Theodorolea; Gabriela Stanc; Christos Iavazzo; Elissaios Kontis (Folia Medica)
The rectovaginal septum is a rare location for gastrointestinal stromal tumors (GIST) to occur. The aim of this study was to present a case of synchronous local recurrence of solitary liver metastasis originating from an extra gastrointestinal tumor (E-GIST) of the rectovaginal space. A 55-year-old woman, with a medical history of a resected meningioma, was referred to our department due to a 5 cm solitary liver metastasis located within the left lateral segment. The patient had undergone a transvaginal resection of a low-risk E-GIST 6 months prior without receiving adjuvant chemotherapy. The patient underwent a synchronous laparoscopic left lateral hepatectomy and a transvaginal resection with posterior vaginal wall reconstruction. Her postoperative course was uneventful and was discharged on the fifth postoperative day. The histological examination of the vaginal lesion revealed the development of neoplasm with pathological characteristics consistent with the initial histology expect for a mitotic index exceeding >20%. Liver histology report also included a high-risk GIST with CKIT (+), DOG1 (+), ki67 ≥30%, high mitotic activity and clear resection margins. The patient was referred for adjuvant chemotherapy. E-GISTs are rare neoplasms with low malignant potential. However, these tumors may exhibit metastatic potential and require aggressive treatment.